PCT testing in sepsis protocols - Valencia, Luke (Frontiers in Analytical Science, 2023)
Septicemia is a prominent disease with a mortality rate of over 20%, making it one of the most expensive illnesses for hospitals in the United States. Parafollicular cells release procalcitonin (PCT) in response to severe bacterial infection. This literature review of current publications attempts to assess procalcitonin as a potential addition to sepsis protocols and to identify recommendations when implementing PCT into sepsis workups. Incorporation of the PCT could significantly reduce the financial burden, antibiotic usage, and mortality rates in sepsis cases.